Knowledge Of Post Natal Mothers On Identıfıcatıon Of Neonatal Danger Sıgns - Mr. Vishal R. Yande, Mrs. Sheetal Avinash Kadam, Ms. Steffy Elizabeth, Ms. Teena Cherin, Ms. Tintu Thomas, Mr. Mobin Mathew (International Journal of Advanced Science and Technology, 2020)
Background :- Only the mother can identify and control the ’problems in neonatal period. The most important time for improving the rate of survival is first 28 days of life (the neonatal period). Every year 10 millions of under five children die. Most of them die in their neonatal period. and from that one-third of deaths occur on the first day after birth . Because of failure to identify danger signs in neonates by mother and not receving care in newborn illness death occurs. Material and Methods:- A present descriptive type of study was conducted with quantitative approach. 100 post -natal mothers were selected by purposive sampling technique with an objective to assess the knowledge level of post-natal mothers on neonatal danger signs. After getting the permission from ethical committee of institute and concern authority data collection started. written consent obtained from mothers .data was collected by using structured questionnaire consisting section-1 contain sociodemographic data of mothers and section -2 consist knowledge questionnaire on neonatal danger signs. Collected data was analysed as per objectives of the study. .Results: Knowledge of post natal mothers regarding identification of neonatal danger signs, majority of mothers 12 (12%) had good, 51 (51%) had average knowledge, and 37(37%) had poor knowledge. A significant association was not found between level of knowledge and socio-demographic variables. Conclusion:- it concludes that providing health education and advice for mothers in antenatal visit, immediately after delivery and during PNC follows-up on Neonatal Danger Sign is very essential for improving the knowledge.